Cellulose acetate nanofibers embedded with AgNPs anchored TiO2 nanoparticles for long term excellent antibacterial applications. (1st March 2019) - Jatoi, Abdul Wahab; Kim, Ick Soo; Ni, Qing-Qing
Highlights: Synthesis of TiO2 /AgNP nanoparticles by dopamine hydrochloride. Incorporation of TiO2 /AgNP nanoparticles into cellulose acetate nanofibers. The CA/TiO2 /AgNP nanofibers fabricated for long term excellent antibacterial uses. The CA/TiO2 /AgNP nanofibers are expected to reduce chances of argyria and argyrosis . The CA/TiO2 /AgNP nanofibers depicted antibacterial properties for upto 72 h. Abstract: Silver nanoparticles (AgNPs) are effective antimicrobial agents however excess release of silver causes argyria and argyrosis . An strategy to avoid these detrimental side effects is immobilization of AgNPs on several organic and inorganic substrates. Herein, we propose immobilization of AgNPs on TiO2 nanoparticles by an environmentally green process subsequently incorporating the TiO2 /AgNP into cellulose acetate (CA) nanofiber matrix. The TiO2 /AgNP nanocomposite particles were prepared by coating TiO2 nanoparticles with polydopamine hydrochloride followed by a treatment in AgNO3 solution. Subsequently, the TiO2 /AgNP nanocomposites were added into CA solution and electrospun to fabricate CA/TiO2 /AgNP composite nanofibers. The samples were characterized by XRD, TEM, XPS, SEM, EDX, FTIR and antibacterial assays. Synthesis of TiO2 /AgNP and its loading into CA nanofibers was confirmed by XRD, XPS, TEM and EDX analysis. SEM images indicated regular morphology of the nanofibers. The antibacterial test results confirmed CA/TiO2 /AgNP composite nanofibers having excellent antibacterial performances for 36 h and substantial bacterial growth inhibition for 72 h.